2015
DOI: 10.1242/jeb.126235
|View full text |Cite
|
Sign up to set email alerts
|

Power amplification in an isolated muscle-tendon is load dependent

Abstract: During rapid movements, tendons can act like springs, temporarily storing work done by muscles and then releasing it to power body movements. For some activities, such as frog jumping, energy is released from tendon much more rapidly than it is stored, thus amplifying muscle power output. The period during which energy is loaded into a tendon by muscle work may be aided by a catch mechanism that restricts motion, but theoretical studies indicate that power can be amplified in a muscle-tendon load system even i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 26 publications
5
48
0
1
Order By: Relevance
“…This assertion is in agreement with models of muscle-tendon interaction, which predict that the force-length relationship should shift rightward and become skewed toward initial sarcomere lengths on the ascending limb as series elastic compliance increases (Lieber et al, 1992). The plantaris muscle of the bullfrog has a high fixed-end compliance (∼30%; Sawicki et al, 2015b), but avoids operating at fibre lengths on the ascending limb during the take-off phase of jumping by beginning at lengths on the descending limb. Force attenuation in this muscle is mitigated by actively shortening from lengths beyond optimum length onto the plateau region prior to take-off (Azizi and Roberts, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…This assertion is in agreement with models of muscle-tendon interaction, which predict that the force-length relationship should shift rightward and become skewed toward initial sarcomere lengths on the ascending limb as series elastic compliance increases (Lieber et al, 1992). The plantaris muscle of the bullfrog has a high fixed-end compliance (∼30%; Sawicki et al, 2015b), but avoids operating at fibre lengths on the ascending limb during the take-off phase of jumping by beginning at lengths on the descending limb. Force attenuation in this muscle is mitigated by actively shortening from lengths beyond optimum length onto the plateau region prior to take-off (Azizi and Roberts, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…In contractions of a muscle tendon unit with simulated loads, low loads relative to P 0 (∼17.5% P 0 ) tend to produce the greatest amount of muscle power amplification (Sawicki et al, 2015). These relatively low forces that maximize performance as measured by power amplification (Sawicki et al, 2015) also maximize thermal performance, as we have shown (Table 1, Fig.…”
Section: Impacts On Elastically and Muscle-powered Movementssupporting
confidence: 51%
“…Elastic systems in which relatively large muscles are moving small loads are optimized for power amplification, but not muscle work (Sawicki et al, 2015). In contractions of a muscle tendon unit with simulated loads, low loads relative to P 0 (∼17.5% P 0 ) tend to produce the greatest amount of muscle power amplification (Sawicki et al, 2015).…”
Section: Impacts On Elastically and Muscle-powered Movementsmentioning
confidence: 99%
See 2 more Smart Citations